Characterization of HIV-1 Epidemic in Kyrgyzstan - Sivay, Mariya V.; Totmenin, Alexei V.; Zyryanova, Daria P.; Osipova, Irina P.; Nalimova, Tatyana M.; Gashnikova, Mariya P.; Ivlev, Vladimir V.; Meshkov, Ivan O.; Chokmorova, Umut Z.; Narmatova, Elmira; Motorov, Ulukbek; Akmatova, Zhyldyz; et al. (Frontiers in Microbiology, 2021)
Kyrgyzstan has one of the highest rates of HIV-1 spreading in Central Asia. In this study, we used molecular-epidemiological approaches to examine HIV-1 epidemic in Kyrgyzstan. Samples were obtained from HIV-positive individuals who visited HIV/AIDS clinics. Partial pol gene sequences were used to identify HIV-1 subtypes and drug resistance mutations (DRM), and to perform phylogenetic analysis. Genetic diversity and history reconstruction of the major HIV-1 subtypes were explored using BEAST. This study includes analysis of 555 HIV-positive individuals. Study population was equally represented by men and women aged 1-72 years old. Heterosexual transmission was the most frequent, followed by nosocomial. Men were more likely to acquire HIV-1 during injection drug use and while getting clinical services, while women were more likely to be infected through the sexual contacts (P<0.01). Heterosexual transmission was the more prevalent among individuals 25-49 years old; individuals over 49 years old were more likely to be persons who inject drugs (PWID). The major HIV-1 variants were CRF02_AG, CRF63_02A, and sub-subtype A6. Major DRM were detected in 26.9% of the study individuals; 62.2% of those had DRM to at least two ARV drug classes. Phylogenetic analysis revealed a well-defined structure of CRF02_AG indicating locally evolving sub-epidemics. The lack of well-defined phylogenetic structure was observed for A6. The estimated origin date of CRF02_AG was 1997.1, CRF63_02A - 2004.4, and A6 - 1995.6. A rapid evolutionary dynamic of CRF02_AG and A6 among Kyrgyz population since mid-90s was observed. We observed the high levels of HIV-1 genetic diversity and drug resistance in the study population. Complex patterns of HIV phylogenetics in Kyrgyzstan were found. This study highlights the importance of molecular-epidemiological analysis for HIV-1 surveillance and treatment implementation to reduce new HIV-1 infections.